2019
DOI: 10.5194/isprs-archives-xlii-2-w13-1121-2019
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumental Basis for Multispectral Lidar With Spectrally-Resolved Distance Measurements

Abstract: Commission II, WG II/3 KEY WORDS: Hyperspectral and multispectral LiDAR, reflectorless distance measurement, remote material probing, laser scanning, femtosecond laser ABSTRACT:Hyperspectral solutions augment laser scanning technology with material probing capabilities by measuring target reflectance along with topography. We propose a novel instrumental basis that enables also spectrally-resolved distance measurement with sufficient sensitivity as to access dispersive phenomena on the reflecting target and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The distance of the target is calculated from the phase difference of the electric beat notes output by the two APDs. 21 According to the radar equation, 22,23 the reflectance R of a target can be expressed by a function of the received optical power P r and the transmitted optical power P t of the LiDAR system as R = K • P r /P t . The coefficient K depends on the measurement geometry (mainly incidence angle and ranging distance), atmospheric attenuation, and several system constants (e.g., aperture of the collection optics, responsivity of the optical detector).…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…The distance of the target is calculated from the phase difference of the electric beat notes output by the two APDs. 21 According to the radar equation, 22,23 the reflectance R of a target can be expressed by a function of the received optical power P r and the transmitted optical power P t of the LiDAR system as R = K • P r /P t . The coefficient K depends on the measurement geometry (mainly incidence angle and ranging distance), atmospheric attenuation, and several system constants (e.g., aperture of the collection optics, responsivity of the optical detector).…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…The distance of the target is calculated from the phase difference of the electrical beat notes output by the two APDs. 48 Forty band-pass filters mounted in eight filter wheels provide two different spectral configurations (Fig. 2) within the spectral range of the SC-OFC.…”
Section: Experimental Setup and Determination Of Spectramentioning
confidence: 99%
“…The other portion of the filtered laser beam is focused on the reference APD. The distance of the target is calculated from the phase difference of the electrical beat notes output by the two APDs 48 . Forty band-pass filters mounted in eight filter wheels provide two different spectral configurations (Fig.…”
Section: Experimental Setup and Determination Of Spectramentioning
confidence: 99%
“…13 A novel approach to multispectral LiDAR based on a femtosecond laser supercontinuum has been proposed in the past, providing both spectrally-resolved phase and power observations of the optical signals backreflected from natural targets. 14 These observations enable deriving distance and reflectance spectral signatures defined by the target material. This work showed that the distance spectral signature complements the reflectance information, thus both signatures can jointly enhance material classification compared with standard multispectral approaches.…”
Section: Introductionmentioning
confidence: 99%